Enhancing Early Identification of Speech-Language-Hearing Delays Through Interprofessional Peer Teaching in a Communication Sciences and Disorders Graduate Training Program. - Lopez, Leslie C.; Guidry, Megan (American Journal of Audiology, 2024)
Introduction: In the current health care landscape, a paradigm shift toward team-based care is underway. Integrating interprofessional education experiences into graduate communication sciences and disorders (CSD) programs is essential to cultivate collaborative skills and prepare future professionals for the interprofessional demands of the field. Within this context, peer teaching has emerged as a noteworthy strategy to promote learning. This study aims to contribute to this evolving field by reporting the impact of an interprofessional (speech-language pathology and audiology) peer teaching educational intervention on physician assistant (PA) students' knowledge of speech-language-hearing developmental milestones and developmental screening. Method: A quantitative, descriptive methodology with a pretest, posttest interventional design was utilized to assess the impact of a CSD peer-led educational intervention on the knowledge of 35 PA students. The perceived satisfaction of the PA students with the peer-led educational experience was also evaluated. Results: Data analysis revealed a significant increase on knowledge posttest scores compared to pretest scores. PA students also reported an overall positive peer learning experience. Conclusion: The collaboration between speech-language pathology, audiology, and PA students through peer teaching holds significant importance in the context of pediatric primary care, and for CSD graduate trainings programs interested in improving educational experiences that tailor to interprofessional learning and practice.